T cell epitope mapping reveals immunodominance of evolutionarily conserved regions within SARS-CoV-2 proteome - Cansu Cimen Bozkus; Matthew Brown; Leandra Velazquez; Marcus Thomas; Eric A. Wilson; Timothy O’Donnell; Anna Kaminska; Denis Ruchnewitz; Douglas Geertz; Yonina Bykov; Julia Kodysh; Kasopefoluwa Y. Oguntuyo; et al. (iScience)
Summary: Understanding the breadth and functional profile of T cell responses is crucial for assessing their role in immune surveillance of emerging SARS-CoV-2 variants. Sampling healthy individuals, we profiled the kinetics and polyfunctionality of T cell immunity elicited by mRNA vaccination. Modeling of anti-spike T cell responses against ancestral and variant strains suggested epitope immunodominance and cross-reactivity as major predictive determinants of T cell immunity. To identify immunodominant epitopes, we comprehensively mapped CD4+ and CD8+ T cell epitopes within non-spike proteins using samples from convalescent patients. We found that immunodominant epitopes mainly resided within regions that were minimally disrupted by emerging mutations. Conservation analysis across human coronaviruses and in silico alanine scanning highlighted the functional importance of mutationally constrained immunodominant regions. Collectively, these findings identify immunodominant T cell epitopes across the SARS-CoV-2 proteome that may enhance immune surveillance against emerging variants and inform next-generation vaccine designs providing broader and more durable protection.